Malaysian Communist Party (Mcp): Internationally Lack of Support and Locally Disoriented - Mohd Rizal Mohd Yaakop; Sharifah Aluya Ali; Sharifah Sabrina Ali; Iing Nurdin; Ahmad Redzuan Mohamad; Mohd 'Azmi Mohd Razif (Human Resources Management Academic Research Society (HRMARS), 2025)
An early communist movement in Malaysia (formerly Malaya) was a reaction to the emergence of the ideology and its movement in Indonesia and China. Malaysian Communist Party (MCP) was established in 1930 as a political and militant movement - mainly inspired by the communist Party in the Republic of China - though we cannot fully admit that the party was fully controlled by China or other communist countries. MCP’s aim was to gain independence from the British colonialization but at the same time also aiming at securing the Chinese community in the country. MCP was popular among the Chinese but not the Malays in Malaysia. The methodology of this research is based on declassified data gathered from British National Archive (which later footnoted as CAB, CO, WO etc) and various secondary readings. This paper argues that although MCP was inspired and instigated by international communist movement it was actually problematic at a local (or societal) level- the failure was mainly in domestic political sphere. In relation to this, it would appear that the MCP strategy to conjunct international (and regional) forces cannot meet its domestic needs. The lessons from outside were actually not consistent with developments from within; they not well fitted in with Malaysian facts.